THE INCORPORATION OF COMMUNICATION SKILLS IN PUBLIC SPEAKING COURSE SYLLABUS AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Luthfia Putri Utami; Siti Drivoka Sulistyaningrum (University of Muhammadiyah Malang, 2022)
Communication skills have been considered as an essential skill and element of employability in the 21st-century, because these skills are needed for workplace adaptability competitiveness. Therefore, it also affects the field of education and integrating communication skills in the curriculum are urgently needed. Hence, this study aimed to explore the extent to which communication skills are incorporated, along with the syllabus components that have been incorporated into communication skills. To conduct this content analysis, the statements (words, phrases, and sentences) in the syllabus were collected and 12 out of 35 indicators of communication skills are employed. The data source of this study was the syllabus for the 4th semester of public speaking course in 2020 at University X in Jakarta. It was found that 11 out of 12 indicators were incorporated into the syllabus. Moreover, it turned out the indicators appear to be incorporated in 7 out of 12 components of syllabus, which are: Course Identification, Course Description, Learning Outcomes, Course Goal, Materials, Learning Methods, and Task Description. The result reveals that the communication skills are already incorporated but still limited and the syllabus needs further revisions in order to meet the communication skills indicators.